Impacto sociocultural causado por la actividad agroturística en el Centro Recreacional Angelita del Cantón Buena Fe, año 2019 - Cedeño Bernita, Katherine Paola (2020)
This research work is based on the theme "SOCIOCULTURAL IMPACT CAUSED BY AGROTURISTIC ACTIVITY IN THE" ANGELITA "RECREATIONAL CENTER OF CANTON BUENA FE, YEAR 2019" with the purpose of improving the sociocultural impact of the "Angelita" recreational center, in order to favor to social development In this research project it is fragmented by different chapters which are specified as follows: CHAPTER I: the subject is analyzed, it is spoken in a research context, which is divided into contextualization at international, national, local and institutional levels of different authors, after this it was established what is the problem that must be developed, also The limitations are discussed, the objectives can also be found in order to establish the justification for this project. CHAPTER II: The following chapter also called theoretical or referential framework, is directed by several criteria of different authors, obtained from numerous sources, which has the definitions and concepts of each of the arguments designed to investigate, also within this category of position Theoretical and category of analysis can reach through this to the personal screaming of each of the hypotheses and variables. CHAPTER III: This covers the tabulation of data from the surveys towards the inhabitants of the canton, the investigation also shows the statistical tables and graphs that allow us to verify and verify the responses obtained and showing their results in order to obtain the conclusions and recommendations. CHAPTER IV: In this last chapter, the proposal and what is going to be carried out based on the opinions of the inhabitants to give an improvement, establishing an analysis to prevail the proposals, to improve the sociocultural impact of the recreational center.